EFEKTIVITAS MEDIA LEAFLET TERHADAP PENGETAHUAN PENGGUNAAN ANTIBIOTIK DI KABUPATEN BANGKA - Lana Sari; Ratih Puspita Kusumadewi Purba (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2024)
Antibiotics are medications that physicians often prescribe to treat and prevent bacterial infections. Antibiotic resistance may be predisposed by improper antibiotic usage practices. The public’s ignorance about the proper use of antibiotics is the cause of this. The quality of a patient’s health will improve if antibiotics are used judiciously and in accordance with prescribed guidelines. If antibiotics are not used as directed, their efficacy will be diminished and the expense of recovery therapy will rise. To guarantee treatment efficiency and avoid resistance, it is essential to understand and be aware of the patients receiving antibiotics. This research sought to determine the efficacy of leaflet media in Bangka Regency, Bangka Belitung Islands Province, in promoting antibiotic use knowledge. A validity-tested questionnaire from previous research served as the study’s instrument. Quasi-experimental in nature, this kind of study uses a pretest-posttest design involving only one group. It also has a quantitative analytical focus. An unintentional sampling strategy combined with a non-random sampling method was employed in the study to acquire data. 166 people served as the study’s subjects. A questionnaire was used as the measuring tool in the study. It was sent to the participants’ community in two assessments, one month apart, and included leaflet media as an intervention. Analytical tests, both univariate and bivariate, were used to examine the data. The results show that there is a substantial difference in knowledge between the pretest and posttest, and that leaflet media is successful in increasing people’s awareness of antibiotics in Bangka Regency. The P-value is 0.001< 0.05.